The returns to empowerment in diversified rural household: Evidence from Niger - Wouterse, Fleur (International Food Policy Research Institute, 2017)
Niger is a landlocked Sahelian country, two-thirds of which is in the Sahara Desert. Although only one-eighth of the land considered arable, the overwhelming majority of Niger’s households is involved in rain-fed agriculture largely for subsistence. Given erratic rainfall and low soil fertility, most smallholders fail to produce enough food to meet household requirements. Income diversification is thus the norm among these rural households and different income-generating activities offer alternative pathways out of poverty for households as well as a mechanism for managing risk in an uncertain environment. Empowerment is likely to be an important factor affecting the ability of households to diversity their activity portfolio and may also affect activity-incomes and thereby household welfare. In this study, I use new household- and individual-level empowerment data from the Tahoua region of Niger and regression analysis to quantify the effects of a range of human capital measures including empowerment on the activity portfolio and activity incomes of rural households. My findings reveal that empowerment in particular plays an important role in enabling households to engage in mixed diversification strategy, which combines staple cropping with nonfarm activities and migration. This is a “last resort” strategy for households in lower landholding quintiles to ensure food security and complement an inadequate resource base. Controlling for activity choice, three empowerment indicators in particular—confidence, group membership, and tenure security—strongly and positively affect income from staple and cash cropping, which on average makes up about 90 percent of household income. In fact, empowerment is the only human capital variable that strongly and positively affects total household income, opening up interesting avenues for policy interventions aimed at augmenting a household’s noncognitive ability through, for example, leadership training or encouraging producer group membership—to increase incomes of the rural poor.